عناية الائمة النقاد بعلل المتون "دراسة تطبيقية من خلال شرح علل الترمذي لابن رجب - تريعه, يوسف (جامعة الوادي - University of Eloued, 2021)
تناولنا في هذا البحث الذي هو بعنوان: عناية الائمة النقاد بعلل المتون "دراسة تطبيقية من خلال " شرح علل الترمذي لابن رجب" أحد أهم القضايا التي تٌطرح دائما، والتي هي: مدى عناية أئمة الحديث بمتون الحديث ونقدها وتعليلها، وذلك من خلال: "شرح علل الترمذي" لابن رجب. ولا يمكن أن نُثبت اهتمام الائمة بمتون الحديث الا بدراسة تطبيقية على بعض المتون التي تعرض لها ابن رجب في كتابه. وقصدنا من خلال هذه الدراسة: تحديد ملامح مناهج الائمة في التعامل مع علل المتون، وذلك من خلال قواعد تدل على رسوخ ووضوح منهجهم في التعامل مع علل المتون. ومن أجل أن نعرف هذه القواعد التي أُستعملت في تعليل المتون بشكل مستقل عن الاسانيد كانت دراستنا بالشكل الآتي: أولا: عناية الائمة بمتون الحديث وعلاقة المتن بالعلل ثانيا: أهم أنواع علل المتون من خلال كتاب " شرح علل الترمذي"، وهذه الأنواع المختارة هي: العلل المتعلقة بالإدراج والشذوذ والنكارة والاضطراب في المتن. من خلال هذه الدراسة يتضح لنا أنه قد يُحكم على الحديث من خلال تعليل متنه دون دراسة إسناده. Abstract : In this research, which is entitled: The Care of the Critical Imams with the Reasons of the Text “An Applied Study through “Explanation of the Reasons of Al-Tirmidhi by Ibn Rajab”, one of the most important issues that are always raised, which is: the extent to which the Imams of hadith care and interest in the texts of the hadith, their criticism and justification, through: Explanation of the ills of al-Tirmidhi by Ibn Rajab. In order to know these rules and evidence that they used in studying the texts and their explanation independently of the chains of transmission, our study was as follows: First: The imams’ attention to the text of hadith and the relationship of the text to the ills Second: The most important types of ills of the texts through Ibn Rajab’s book explaining the ills of al-Tirmidhi, and these selected types were as follows: The issues related to the inclusion in the text. Issues related to anomalies and oddities in the text. Issues related to the disorder in the text.
The Care of the Critical Imams with the Reasons of the Text “An Applied Study through “Explanation of the Reasons of Al-Tirmidhi by Ibn Rajab“
مقال
Keywords: العلل ; المتون ; ابن رجب ; الائمة النقاد ; الترمذي; Reasons; the Text; Ibn Rajab; the Critical Imams; Al-Tirmidhi